Comparison Between GAMIL, and CAM2 on Interannual Variability Simulation - 杨军丽 王斌 郭裕福 万慧 季伸贞 (Advances in atmospheric sciences, 2007)
Recently, a new atmospheric general circulation model （GAMIL： Grid-point Atmospheric Model of IAP LASG） has been developed at the Institute of Atmospheric Physics （IAP）, Chinese Academy of Sciences （CAS）, which is based on the Community Atmospheric Model Version 2 （CAM2） of the National Center for Atmospheric Research （NCAR）. Since the two models have the same physical processes but different dynamical cores, the interannual variability simulation performances of the two models are compared. The ensemble approach is used to reduce model internal variability. In general, the simulation performances of the two models are similar. Both models have good per- formance in simulating total space-time variability and the Southern Oscillation Index. GAMIL performs better in the Eastern Asian winter circulation simulation than CAM2, and the model internal variability of GAMIL has a better response to external forcing than that of CAM2. These indicate that the improvement of the dynamic core is very important. It is also verified that there is less predictability in the middle and high latitudes than in the low latitudes.